Morphological and Flowering Characteristics of Shallot (Allium cepa Var. Aggregatum) in Response to Gibberellic Acid and Vernalization - Marlin, Marlin; Hartal, Hartal; Romeida, Atra; Herawati, Reny; Simarmata, Marulak (Emirates Journal of Food and Agriculture, 2021)
Shallot plants have variations in morphological and flowering characters. Flowering ability can be induced by the treatment of gibberellic acid (GA3) and exposing to cold temperature (vernalization). The objectives of the research were to determine the effect of GA3 and vernalization on the morphological and flowering characters of 5 shallot varieties. Field study was organized in a completely randomized block design with three replications to evaluate the responses of 5 varieties of shallots (Bauji, Bima Brebes, Super Philip, Tajuk, and Thailand) to GA3 with the concentrations ranged from zero to 150 mg L-1. Plants were maintained for 65 days until harvesting. The second study was organized in a completely randomized design with 3 replications to evaluate the responses of the five varieties of shallot to vernalization. The vernalization of shallot bulbs were done at 8 o C for 6 weeks. The results indicated that a Super Phillip variety showed the highest response to GA3 observed in the number of leaves and bulbs. At 100 mg L-1 of GA3 increased the plant height up to 45.74 cm. The results from the second study showed that vernalization was effective to increase flowering only on the Ilokos variety. But the other varieties were not sensitive to vernalization. Based on morphological and flowering characters, 5 varieties of shallots were clustered into 3 groups, namely: sensitive flowering included Bentanis, Bma Brebes and Tajuk variety, medium sensitive flowering included Ilokos variety, and non-sensitive flowering included Sumenep variety.